Formação de professores de Geografia na Universidade Federal de Uberlândia na perspectiva da educação inclusiva - Duarte, Laura (2022)
The research aims to identify whether the training currently offered by the Degree in Geography of the Universidade Federal de Uberlândia for its students enables, albeit initially, the graduates to practice inclusive education in the classroom. For this, the dissertation began its scientific incursion by surveying a primary theoretical framework, for the purpose of analyzing the history of inclusive education in Brazil, focusing on public policies developed from the 1988 Constitution, and the correlation between the teaching of Geography and inclusive education, to understand the importance of this discipline in student education. It is a plural formation of a graduate capable of promoting teaching, research and extension activities for the formation of reflective, critical and participant students at school and in the community. An analysis of the current curriculum of the Degree in Geography at UFU was also carried out and the offer of the Libras discipline, mandatory, and the discipline Teaching of Geography and Inclusive Learning, optional, was identified. Finally, there was a data collection, interviews, with two groups of subjects, teachers of the Licentiate Course in question and former students who currently teach classes in regular education. In summary, teachers believe in the need for inclusive education, but they do not have technical knowledge and do not usually encourage initiatives in their academic cycle that enable debates and practices aimed both at their own qualification and at the training of students who will become licensed in Geography. However, some subjects claimed to talk about the subject in the classroom, but without much depth. For graduates, the qualification focused on inclusive education was also not sought after. Only one of the participants answered that he had taken a mini course on teaching methodology for blind and low vision students. These teachers, at the time they attended the Degree in Geography, did not receive any incentive and/or relevant training.